Case Report: Early diagnosis of lethal multiple pterygium syndrome with micrognathia: Two novel mutations in the CHRND gene - Chen, Caiyuan; Han, Jin; Xue, Jiaxin; Li, Ru; Chen, Guilan; Yang, Xin; Tang, Jiajie; Li, Fucheng; Li, Dongzhi (Frontiers in Genetics, 2023)
Lethal multiple pterygium syndrome (LMPS) is a rare disease with genetic and phenotypic heterogeneity and is inherited in an autosomal recessive (AR) pattern. Here, we have presented clinically significant results describing two novel mutations of CHRND gene: NM_000751.2: c.1006C>T p.(Arg336Ter) and NM_000751.2:c.973_975delGTG p.(Val325del), and measurement of the facial angle for determining micrognathia by prenatal diagnosis in the first trimester of pregnancy for a LMPS case. In conclusion, this report complements the spectrum of genetic variants and phenotype of LMPS and provides reliable recommendation for the counseling of future pregnancies in families with the disease.